Radionuclide transfer to wildlife at a 'Reference site' in the Chernobyl Exclusion Zone and resultant radiation exposures. (January 2020) - Beresford, N.A.; Barnett, C.L.; Gashchak, S.; Maksimenko, A.; Guliaichenko, E.; Wood, M.D.; Izquierdo, M.
Abstract: This study addresses a significant data deficiency in the developing environmental protection framework of the International Commission on Radiological Protection, namely a lack of radionuclide transfer data for some of the Reference Animals and Plants (RAPs). It is also the first study that has sampled such a wide range of species (invertebrates, plants, amphibians and small mammals) from a single terrestrial site in the Chernobyl Exclusion Zone (CEZ). Samples were collected in 2014 from the 0.4 km 2 sampling site, located 5 km west of the Chernobyl Nuclear Power complex. We report radionuclide ( 137 Cs, 90 Sr, 241 Am and Pu-isotopes) and stable element concentrations in wildlife and soil samples and use these to determine whole organism-soil concentration ratios and absorbed dose rates. Increasingly, stable element analyses are used to provide transfer parameters for radiological models. The study described here found that for both Cs and Sr the transfer of the stable element tended to be lower than that of the radionuclide; this is the first time that this has been demonstrated for Sr, though it is in agreement with limited evidence previously reported for Cs. Studies reporting radiation effects on wildlife in the CEZ generally relate observations to ambient dose rates determined using handheld dose meters. For the first time, we demonstrate that ambient dose rates may underestimate the actual dose rate for some organisms by more than an order of magnitude. When reporting effects studies from the CEZ, it has previously been suggested that the area has comparatively low natural background dose rates. However, on the basis of data reported here, dose rates to wildlife from natural background radionuclides within the CEZ are similar to those in many areas of Europe. Highlights: Large range of species sampled from a site within the Chernobyl Exclusion Zone. Transfer parameters for poorly-studied organisms provided. Contribution of different radionuclides to dose demonstrated. Ambient dose rate may be more than an order of magnitude lower than total dose rate. Transfer of stable elements differed to that of radioelements.